Manajemen Risiko Kesehatan Kerja Melalui Health Risk Assessment di Laboratorium Assay Departemen Geoscience PT X - Adhitya Chandra Setyawan; M.Zulfikar Asumta; Herin Mawarti; Nasrudin Nasrudin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the implementation of occupational health risk management through Health Risk Assessment (HRA) in the Assay Laboratory of the Geoscience Department of PT X and identify barriers, enablers, and managerial implications. This research method uses a qualitative approach with a single case study design to describe and analyze the implementation of Health Risk Assessment (HRA) in the Assay Laboratory of the Geoscience Department of PT X. Data were collected through in-depth interviews, observations, document review, and triangulation, with participants selected using purposive sampling and snowball sampling. Data validity was maintained through member checking, audit trails, and peer debriefing. Data analysis followed the Miles, Huberman, and Saldana (2014) framework, which includes data condensation, data display, conclusion drawing and verification, to generate key themes related to the effectiveness, barriers, and managerial implications of HRA implementation. The results indicate that the implementation of Health Risk Assessment (HRA) in the Assay Laboratory of PT X is able to identify key potential hazards, such as exposure to hazardous chemicals, radiation, and ergonomic and psychosocial risks. The implementation of the HIRA method successfully mapped risk levels from moderate to extreme, thus facilitating management in determining control priorities. Control efforts through chemical substitution, the use of fume hoods, the implementation of standard operating procedures (SOPs), and the mandatory use of personal protective equipment (PPE) proved effective in reducing occupational risk levels. Worker health surveillance demonstrated stable physiological conditions, indicating the program's effectiveness in preventing occupational diseases. Overall, the implementation of the HRA strengthened the workplace safety culture while supporting the continuity of laboratory operations in accordance with OHS standards.